Prevalence of Temporomandibular Disorder and its association with anxiety in academics: a cross-sectional study - Bianca Paludo; Paula Comin Trevizan; Nana Abena Asantewaa Boamah; Lilian Rigo (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Temporomandibular disorders (TMD) are a major cause of non-dental pain in the oral and facial regions. OBJECTIVE: This study aimed to determine the prevalence and severity of TMD and anxiety among academics and to investigate the relationship between TMD and its associated factors. DESIGN AND SETTING: This cross-sectional study included a sample of 295 academics undertaking health courses at a university in Brazil. METHODS: The Simplified Anamnesis Index and Beck Anxiety Inventory were used to evaluate TMD and assess anxiety, respectively. Data were statistically analyzed using relative and absolute frequencies of variables. In the bivariate analysis, Pearson’s chi-square test was used, and in the multivariate analysis, raw and adjusted binary logistic regressions were used to obtain the odds ratio (OR) and respective 95% confidence intervals. Statistical significance was set at P < 0.05. RESULTS: The average age of academics was 22.95 (standard deviation ± 6.14) years, predominantly comprising women (82.7%), whites (90.8%), and singles (86.6%). The findings revealed that 81.2% of academics had TMD and 50.5% exhibited symptoms of anxiety. Academics with anxiety were three times more likely to have TMD (OR = 3.6) than those without anxiety. CONCLUSION: A significant association between anxiety and TMD was observed in academics. The prevalence of TMD was high, with academics with anxiety having a high likely to develop TMD. These findings highlight the importance of addressing mental health concerns in addition to physical health, as they are often related.